1995
DOI: 10.1093/infdis/172.5.1261
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Major Histocompatibility Complex Class II Antigens on Monocytes and B Cells Correlates with Disease in Simian Immunodeficiency Virus-Infected Rhesus Macaques

Abstract: Constitutive host factors that influence progression to AIDS are understood poorly. In the macaque model for AIDS, 35 animals infected with simian immunodeficiency virus (SIV) were analyzed for major histocompatibility complex class II antigen expression on blood monocytes and B cells by immunostaining and flow cytometry. Expression varied widely between animals but was constant with time. Level of expression and the proportion of monocytes and B cells that expressed class II were not affected by SIV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…SIV mac251 used in vaginal challenge is more virulent in rhesus macaques than the SIV mac32HJ5 clone. In a study comparing the two viruses directly, it was shown that animals infected with SIV mac32HJ5 were less likely to develop AIDS than animals infected with SIV mac251 [23].…”
Section: Discussionmentioning
confidence: 99%
“…SIV mac251 used in vaginal challenge is more virulent in rhesus macaques than the SIV mac32HJ5 clone. In a study comparing the two viruses directly, it was shown that animals infected with SIV mac32HJ5 were less likely to develop AIDS than animals infected with SIV mac251 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ashworth et al . demonstrated that in simian immunodeficiency virus‐infected rhesus macaques, the pre‐SIV levels of HLA‐DR on monocytes and B‐cells correlated with disease [66]. Significantly more animals developed AIDS in the group with low class II expression than in the group with high expression [66].…”
Section: Discussionmentioning
confidence: 99%
“…However, as Kamp et al mention in their review, the situation may be yet further complicated by the possibility of individual MHC Class II responses being predetermined by the natural expression level of HLA DR within the host [8]. However, as Kamp et al mention in their review, the situation may be yet further complicated by the possibility of individual MHC Class II responses being predetermined by the natural expression level of HLA DR within the host [8].…”
mentioning
confidence: 99%
“…The combination of increased interferon g production, together with the expected reductions in absolute T cell numbers seen in advancing HIV disease, leads to an overall profile of initial increases in interferon g (early HIV infection), which then this proposed mechanism. However, as Kamp et al mention in their review, the situation may be yet further complicated by the possibility of individual MHC Class II responses being predetermined by the natural expression level of HLA DR within the host [8]. However, no data are yet available to say precisely whether or not individuals will have a set pattern of response for a given opportunistic infection, which may itself enhance or suppress MHC Class II expression [9].…”
mentioning
confidence: 99%